DIGITAL MARKETING BASED MODEL OF ULOS WEAVER IN PEMATANG SIANTAR CITY TO SUPPORT LAKE TOBA TOURISM DESTINATIONS - Robert Tua Siregar; Darwin Lie; Christine Loist; Loist Abdi Putra; Yansen Siahaan (Glow: Jurnal Pengabdian Kepada Masyarakat, 2023)
Based on the results of interviews with several weavers, it is known that there are obstacles in developing the ulos craft business that they run. This problem has an impact on the process of making ulos and marketing of ulos which is not optimal. Given the importance of the existence of ulos cloth in supporting the development of Lake Toba tourism and increasing the financial economy of ulos weavers, it is necessary to provide training and assistance to weaving groups in developing ulos handicrafts. The implementation method uses the Participatory Rural Appraisal (PRA) model which emphasizes community involvement in all activities starting from planning, implementing, and evaluating program activities. The output of this service includes increasing partner empowerment which includes increasing knowledge, increasing skills, product quality improvement, product quantity increase, production capacity increase, turnover number increase, management capability improvement, profit increase and standardized product improvement. In accordance with the results of interviews after the implementation of community service activities, it is known that the understanding of Ulos UKM players regarding the use of digital marketing has increased by 95%.